2023
DOI: 10.29333/pr/13003
|View full text |Cite
|
Sign up to set email alerts
|

Determining the graphical literacy levels of the middle school mathematics teachers

Abstract: This study aims to determine the graphical literacy levels of middle school mathematics teachers. The participants of the study consisted of 33 middle school mathematics teachers working in different provinces. The data of the study were collected with the help of the graphical literacy test created by the researchers. The data were analyzed by content analysis method. As a result of the study, it was seen that the teachers were more successful in the questions that required reading the data in the graph. It h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…Patahuddin and Lowrie (2019) examined teachers' ability to interpret line graphs and found that the teachers do not possess the SCK to answer high-level questions about interpreting the line graphs. In another study, Uyanik et al (2023) investigated teachers' specialized knowledge in the evaluation of graphs and found that more than half of the teachers presented either incomplete or incorrect evaluations. Ozmen et al (2020) found that students could not identify the incorrect graph types and the errors in the graph.…”
Section: Content Knowledge (Ck): Specialized Content Knowledge (Sck)mentioning
confidence: 99%
“…Patahuddin and Lowrie (2019) examined teachers' ability to interpret line graphs and found that the teachers do not possess the SCK to answer high-level questions about interpreting the line graphs. In another study, Uyanik et al (2023) investigated teachers' specialized knowledge in the evaluation of graphs and found that more than half of the teachers presented either incomplete or incorrect evaluations. Ozmen et al (2020) found that students could not identify the incorrect graph types and the errors in the graph.…”
Section: Content Knowledge (Ck): Specialized Content Knowledge (Sck)mentioning
confidence: 99%